Profiling feedback antecedents in higher education students: a person-oriented perspective - Sjølie, Ela; Johnsen, Mette Mari Wold; van Petegem, Peter (Frontiers in Education, 2024)
The ability to give, receive and process feedback is essential for higher education students not only during their studies, but also for their future work life. Despite the extensive amount of research on feedback in education, there is limited research on feedback skills as collaborative skills and on what might influence these skills. Through surveying a large sample of 2,907 university students who worked in self-managed project teams, this study explores how individual characteristics as antecedents relate to students’ perceived feedback skills. We use a person-oriented approach to examine how these antecedents relate within students and how these profiles relate to perceived feedback skills. In addition to reliability, confirmatory factor analysis provided evidence for the structural validity of a newly developed feedback skills instrument. Five scales were used from existing feedback instruments as antecedents of feedback skills, and these were also found to be valid and reliable. Through a person-oriented approach, we applied a hierarchical and a k-means cluster analysis to create student profiles or groups based on feedback antecedents. We identified five distinct groups of students with common feedback antecedents. The results indicate that the five groups also had different levels of perceived feedback skills. The study contributes to the limited research on the dynamics of giving and receiving feedback from the perspective of students in the context of collaborative learning. It has implications for researchers and practitioners to better understand individual differences and to consider these differences when designing collaborative learning activities and facilitating student teams.